Estabelecimento de uma cana-de-açúcar transgênica superexpressando o gene da canacistatina (CaneCPI-1), uma proteína inibidora de cisteíno-protease - Ribeiro, Carolina Werner (2007)
Sugarcane is a plant of great economical importance, mainly in Brazil, which is currently the largest producer of this crop in the world. However, sugarcane farming has suffered attacks from pests and pathogens, leading to considerable economical losses. Therefore, a number of studies have focused on the development of more resistant sugarcane varieties. Our laboratory has been working on a sugarcane protein (CaneCPI- 1), which is a cystein-protease inhibitor protein. Based on studies that indicate that insects belonging to the order Coleoptera possess cystein-proteases in their mid-gut and with the knowledge that some species of Coleoptera are sugarcane pests, a transgenic sugarcane plant overexpressing the CaneCPI-1 gene was developed under the control of maize ubiquitin promoter. CaneCPI-1 was fused to a His-tag to facilitate further purification through affinity chromatography. The calli transformation was performed through biobalistics. The transformed plants were then selected by polymerase chain reaction. Positive plants were further selected by Semi-quantitative PCR and Western blotting. A transformed plant expressing a His-tagged CaneCPI-1 was selected for purification of the recombinant protein in a nickel column, enabling purification of HISCaneCPI-1 from plant leaves in a single step. The yield was about 6mg of pure protein per kilogram of sugarcane leaves. The HISCaneCPI-1 purified from the transformed sugarcane demonstrated inhibitory activity on the human cysteine protease cathepsin L. These studies demonstrate that the sugarcane can be a safe and viable expression system for recombinant protein production, and are the first step in the establishment of a sugarcane plant that is more resistant to pathogens.